PEMBELAJARAN BERNYANYI SECARA UNISONO DI KELAS VII.1 UPT SMPN 1 KOTO XI TARUSAN - Veni Apri Sopati; Harisnal Hadi; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to describe the singing learning of Unisono in UPT SMP N 1 Koto XI Tarusan. The type of this study is qualitative with descriptive approach. The location of the study is in UPT SMP N 1 Koto XI Tarusan. Technique of collecting data is done by using observation, interview and documentation. Technique of data analisis consist of 1) data reduction, 2) data presentation and 3) drawing a conclusion. Result of the study explains that the singing learning of Unisono is done by using three steps; they are planning, implementation and evaluation. In planning step, teachers prepare learning device that are the learning implementation plan and the learning syllabus. In implementation step, the singing learning of Unisono is done in four meetings with preliminary activity, main activity and closing activity. Evaluation step is done to measure the success of students in singing learning of Unisono by doing research on the criteria of research, namely intonation, articulation, rhythm and compactness. Keywords: Singing, Unisono